The role of posttraumatic stress symptoms on memory complaints and performance in active-duty service members. Issue 1 (2nd January 2023) - Disner, Seth G.; Mattson, Elsa K.; Nelson, Nathaniel W.; Armistead-Jehle, Patrick
Abstract: Objective: Memory complaints are the most common form of cognitive limitation reported by military service members, but prior research suggests that posttraumatic stress symptoms (PTSS) may account for the link between subjective cognitive complaints and objective cognitive performance. The mechanisms underlying this relationship are largely unknown, including whether the finding applies to memory complaints and performance, which clinical dimensions are involved, and how the association varies when memory complaints are non-credible. Method: Using a sample of 196 US military service members, the present study aims to address these gaps by modeling the relationship between objective memory performance and plausible/implausible subjective memory complaints, then evaluating how the association is influenced by PTSS and clinical traits commonly found within PTSS (e.g. depression, anxiety, and somatic concerns). Results: Overall memory complaints were associated with immediate and delayed recall, but both associations were fully mediated by PTSS (95% CI −0.14, −0.01; 95% CI −0.14, −0.02, respectively). Implausible memory complaints, however, were inconsistently linked to memory performance, and no PTSS mediation was observed. Of the clinical traits, only depression moderated the impact of PTSS, specifically by influencing the link between PTSS and overall memory complaints (β = −0.02, SE = 0.004, p < .001). Conclusions: These results corroborate the importance of assessment for PTSS and depression in service members who report subjective memory complaints and highlight how targeted intervention for these conditions may play a key role in the management of memory complaints.